2017 IEEE 10th International Conference on Cloud Computing (CLOUD) 2017
DOI: 10.1109/cloud.2017.93
|View full text |Cite
|
Sign up to set email alerts
|

A Distributed Infrastructure for Democratic Cloud Federations

Abstract: Abstract-Cloud federation is a novel concept that has been drawing attention from research and industry. However, there is a lack of solid proposal that can be widely adopted in practice to guarantee adequate governance of federations, especially in the Public Sector contexts due to legal requirements.In this paper, we propose an innovative governance approach that ensures distributed and democratic control in cloud federations. Starting from FaaS, a recent cloud federation proposal, we propose a blockchain in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 5 publications
0
8
0
Order By: Relevance
“…When looking into the application domain, most of the research (7 articles) discuss the application of blockchain for e-Government in general, discuss the idea, potential benefits, current issues, potential use, approach and evaluation of blockchain adoption [20,25,27,29,[35][36][37]. Blockchain applications in public healthcare received the highest attention, with four articles looking into the possible use of blockchain to Meanwhile, three articles examined the use of blockchain in educational services to overcome the lack of data integration and integrity in the public education sector [7,40,41].…”
Section: Overview Of Selected Articlesmentioning
confidence: 99%
See 1 more Smart Citation
“…When looking into the application domain, most of the research (7 articles) discuss the application of blockchain for e-Government in general, discuss the idea, potential benefits, current issues, potential use, approach and evaluation of blockchain adoption [20,25,27,29,[35][36][37]. Blockchain applications in public healthcare received the highest attention, with four articles looking into the possible use of blockchain to Meanwhile, three articles examined the use of blockchain in educational services to overcome the lack of data integration and integrity in the public education sector [7,40,41].…”
Section: Overview Of Selected Articlesmentioning
confidence: 99%
“…In accordance with the categorization of the systems development research process by Nunamaker et al [34], we identified 11 articles that are focused on providing conceptual frameworks of blockchain utilization in e-Government applications. Some of the articles discuss current issues, the potential benefits, the importance and general vision of adopting blockchain technology to improve public services delivery [20,25,27,29,[35][36][37], and e-voting [12]. Furthermore, Sun et al [43] analyzed the influence of blockchain technology on the smart city development while Maria-Lluïsa and Marsal-Llacuna [30] show how blockchain networks could disrupt the urban context.…”
Section: Overview Of Selected Articlesmentioning
confidence: 99%
“…Platform Type Scalability Azure [29] Ethereum, Corda, Fabric Private Auto scaling on service demand IBM [30] Fabric Private High scalability with IBM cloud AWS [31] Ethereum, Corda, Fabric Private Quick node creation APIs HPE [32] Corda Private Linear scalability with backup facilities Oracle [33] Fabric Private, Consortium Dynamic scaling for all resources SAP [34] Fabric Private High scalability with SAP HANA facilities Google [35] Ethereum, Fabric Private Scaling with Google App Engine [36] Any Democratic governance on data and services Alansari et al [37] Ethereum Finegrained attribute-based access control Alansari et al [38] Ethereum Attribute based access control Yang et al [39] Fabric Differntially-private data sharing DRAMS [40] Ethereum Decentralised runtime monitoring -Margheri et al [41] Ethereum Governance for democratic control -CloudChain [42] Fabric Democratic control on IaaS provisioning ness logic stages. Apart from other conventional BaaS models, Big Data Open Architecture (BDOA) with four layers has been incorporated with this model.…”
Section: Servicesmentioning
confidence: 99%
“…DRAMS [40] proposes a blockchain-based decentralized runtime access monitoring system for a federated cloud in order to ensure that the components that receive, process and exchange access requests can not be subverted. Margheri et al [41] proposed an innovative governance approach, data masking, anonymization and access control monitoring services, to ensure a democratic control of different providers in a cloud federation. On the other hand, CloudChain [42] proposed a blockchain-based democratic infrastructure service provisioning system for a cloud federation ensuring the transparency and immutability in resource and information exchange.…”
Section: Federation As a Servicementioning
confidence: 99%
“…In [13] they proposed the use of blockchain infrastructure to implement a distributed, democratic and trustworthy governance approach in Federation-as-a-Service (FaaS) federations for SUNFISH platform. They focused mainly on the context of the public sector and its legal requirements.…”
Section: Related Workmentioning
confidence: 99%